On Mergers, Divestments, and Options: A Note - Sarig, Oded H. (Journal of Financial and Quantitative Analysis, 1985)
In this note, a loss shared by the security holders of merging firms is pointed out: separate corporate entities provide double protection against future negative cash flows that are partof any production process (e.g., when customer or employee liabilities exceed future income), independent of whether or not debt is used in the corporate capital structure. A merger involvesa relinquishment of this double protection in return for a less valuable single protection: limited liability in the merged corporation against combined negative cash flows.